(untitled) (Gestão & Regionalidade, 2023)
A bill, recently approved by the federal congress and sent to the Senate, could modify the environmental sanitation licensing. The objective of this work is to explore the evolution of environmental impact assessment legislation for environmental sanitation systems to provide technical support for the new environmental licensing framework in the context of sanitation privatization. This bibliographical and documentary study analyzes norms and resolutions representative of the legal framework applicable to environmental and water issues. The results indicate that Brazil has a broad legal scope in environmental and water resources matters, fundamental to guaranteeing guidelines for licensing potentially degrading projects, such as sanitary sewage and water supply systems. Although a scenario of an increase in these projects is foreseen due to the new legal framework for basic sanitation, the new licensing framework is a negative surprise when it excludes them from the list of initiatives submitted to environmental impact assessment.